Successful autologous peripheral blood stem cell transplantation in a Jehovah’s Witness with multiple myeloma: review of literature and recommendations for high-dose chemotherapy without support of allogeneic blood products - Schmitt, Stefan; Mailänder, Volker; Egerer, Gerlinde; Leo, Albrecht; Becker, Sven; Reinhardt, P.; Wiesneth, M.; Schrezenmeier, H.; Ho, Anthony Dick; Goldschmidt, Hartmut; Möhler, Thomas (International journal of hematology, 2008)
We present a case report of a successful high-dose melphalan therapy and autologous stem cell transplantation without the use of allogeneic blood product support in a 70-year-old patient suffering from multiple myeloma. Based on the experience in this case and thorough evaluation of the literature, we consider pre-transplant Hb level of 11-12 g/dl, platelet count higher than 70/nl, good WHO performance status of two and lower and informed consent as important eligibility criteria. During cytopenia recommended supportive measures include growth factor support with erythropoietin and G-CSF, p.o. iron treatment as well as prophylactic use of anti-fibrinloytic agents. Furthermore we discuss additional options that might be considered depending on the individual factors as e.g. pre-transplant collection and cryoconservation of autologous platelet concentrates. Moreover, an analysis of socio-economic issues regarding this procedure is presented. We conclude that allogeneic blood product free transplantation is a feasible procedure that can be offered to the patients belonging to distinct religious groups refusing allogeneic blood products as Jehova´s Witnesses and patients presenting other contraindications for transfusions.